2011
DOI: 10.1016/j.aquatox.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional impact of organophosphate and metal mixtures on olfaction: Copper dominates the chlorpyrifos-induced response in adult zebrafish

Abstract: Chemical exposures in fish have been linked to loss of olfaction leading to an inability to detect predators and prey and decreased survival. However, the mechanisms underlying olfactory neurotoxicity are not well characterized, especially in environmental exposures which involve chemical mixtures. We used zebrafish to characterize olfactory transcriptional responses by two model olfactory inhibitors, the pesticide chlorpyrifos (CPF) and mixtures of CPF with the neurotoxic metal copper (Cu). Microarray analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…in differential regulation as was seen in Tilton et al (2011) and microarray data mining (Maryoung et al, 2014, in review).…”
Section: Molecular Endpointsmentioning
confidence: 91%
See 1 more Smart Citation
“…in differential regulation as was seen in Tilton et al (2011) and microarray data mining (Maryoung et al, 2014, in review).…”
Section: Molecular Endpointsmentioning
confidence: 91%
“…Transcripts expressed during salinity acclimation were compared with gene expression profiles in zebrafish treated with chlorpyrifos (Tilton et al, 2011). Primers were designed using Primer3 software for G protein zgc:101761 (GNA11B) and adrenergic alpha 2C receptor (ADRA2C).…”
Section: Molecular Endpointsmentioning
confidence: 99%
“…Numerous environmental issues have arisen so far due to the excessive use of this chemical compound (3), as it, among other consequences, causes toxic effects in non-target aquatic organisms, especially fish (4). Fish are used to assess the health of aquatic environments and physiological changes occurring as a result of pollution and multiple studies have already established that chlorpyrifos has various detrimental effects on t h e m ( 5 -1 0 ) , s u c h a s n e u r o t o x i c i t y v i a acetylcholinesterase inhibition (11), biochemical and histopathological alterations (12, 13), oxidative stress (12, 14), genotoxicity (15), and olfactory and neurobehavioral injuries (16). It therefore poses a serious threat to aquatic organisms as well as to human health (17).…”
mentioning
confidence: 99%
“…Tilton et al (2008Tilton et al ( , 2011),) exposed zebrafish (Danio rerio) to low concentrations of copper and/or chlorpyrifos. Tilton et al (2008) exposed zebrafish to increasing concentrations of copper (6.3, 16, and 40 g/L) for 24 h and found that the transcription of many genes was altered in response to copper exposure, with the largest number of genes having altered transcription at the highest tested concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Tilton et al (2008) exposed zebrafish to increasing concentrations of copper (6.3, 16, and 40 g/L) for 24 h and found that the transcription of many genes was altered in response to copper exposure, with the largest number of genes having altered transcription at the highest tested concentrations. Tilton et al (2011) exposed zebrafish to copper and/or chlorpyrifos (an organophosphate pesticide) for 24 h and both contaminants showed unique transcriptional signatures. However, when they used a mixture of copper and chlorpyrifos, the transcriptional signature was closer to that of copper, even at high concentrations of chlorpyrifos.…”
Section: Introductionmentioning
confidence: 99%